Poet vs. Philosopher: Shem Tov ben Joseph ibn Falaquera’s significance regarding the antecedents and reception of Maimonides - Babits, Antal (Acta Cultura et Paedagogicae, 2023)
Shem Tov ben Joseph Falaquera (ca. 1225 - ca. 1295) in his youth he was a poet and afterwards declared that he was quitting poetry to devote himself to less frivolous pursuits; but this was perhaps only a figure of speech. His poetry is in contemporary taste, without further distinction. As a philosopher he was not original and did not wish to be. He was also a writer of occasional poems, and probably in the fashion of the time, received gifts from wealthy patrons. This occupation, however, he early abjured as little suited to his taste and temperament. In his mature age, Falaquera declared that to pursue poetry is a dangerous profession as it is not engaged in truth but in beauty and rhetorics instead!